Effect of formalin therapeutic bath on stress indicators in tambaqui - de Araújo, Lucelle Dantas; Chagas, Edsandra Campos; Gomes, Levy de Carvalho; Brandão, Franmir Rodrigues (Pesquisa Agropecuaria Brasileira, 2004)
The formalin has been used to control fish disease, however there are little information on secondary effect of this chemical on fish. The objective of this work was to evaluate the effect of formalin therapeutic concentrations on tambaqui (Colossoma macropomum Cuvier 1818) homeostasis by physiological parameters. Therapeutic baths were carried out in tanks of 100 L with formalin solution at 0, 100, 150, 200 and 250 mg/L and exposures of 0, 30, 60 and 120 minutes; recovery of the animals in water without formalin solution was evaluated after 24 hours. Blood was withdrawn from caudal vein to evaluate glucose, chlorides, sodium, potassium and calcium. Fish did not present stress signs in the formalin concentration of 100 mg/L in all exposure times. Although, baths of 200 and 250 mg/L promote significant increase in glucose levels after 30 minutes exposure. Formalin might be used in bath solutions of 100 and 150 mg/L for 30, 60 and 120 minutes and in baths of 200 and 250 mg/L up to 30 minutes without compromising tambaqui homeostasis.